Marketing of public and business affairs subsystems of socio-economic environment - Adriana Grigorescu (Contemporary Economics, 2008)
The Romanian society is crossing one of the most important stages of its transition toward the integration in the European Union started with January 1st, 2007; this will define the final processes bound for the socio-economic reconstruction. Based on the previous experiences, an assumption rose up that, at this moment in the Romanian society there are two systems - business and public administration, placed on opposite, antagonistic, unfriendly sides. At the same time, there is the opinion that a proper public and private marketing could be the link between them. The link between these systems should make the relation useful to create and handle the cooperation and cooperation climate in these two environments. The paper aims to present the systems, their characteristics, the opinion about the other, the identified link components, and to propose a solution for the link improvement. A small survey of the membersí opinions, in both systems, will be the base of the analysis. The first stage is to analyze each environment as an independent system: business system (BSy) and public administration system (PASy). We will present the structure, characteristics, interactions with other socio-economic components, etc. The second stage will focus on the role of public and private marketing as tools of feedback reaction of the systems to the general environment dynamics. The marketing behavior is typical for the BSy and its level of marketing knowledge is higher than the poor level of marketing knowledge in PASy lacking the marketing attitude about public services.
Keywords: 330